IMPLEMENTATION OF CSR PROGRAMS TOWARD ACHIEVEMENT OF THE SDGs TARGET - Weni Apriliyani; Novita Novita (ACCRUALS (Accounting Research Journal of Sutaatmadja), 2019)
Preparation of this study aimed to evaluate whether CSR program PT Holcim Indonesia Tbk has met the criteria of GRI-Standard and determine whether CSR program PT Holcim Indonesia Tbk is able to support perncapaian SDG's targets in 2030. This study is a qualitative and quantitative research. Research data collection techniques by interviewing the management of PT Holcim Indonesia Tbk namely Community Relations division and the local government. The second data collection techniques is by distributing questionnaires to people who get Holcim CSR program. The results of data analysis in this research produces information that only PT Holcim Indonesia CSR program Tbk economics that has influence on the target perncapaian SDG's. While the social and environmental fields have not been proven to have an effect on the achievement of the target SDG's. The results of the data analysis was due largely Holcim CSR program is only focused on the achievement of the economy and the realization of all the indicators for the achievement of SDG's may have been performed by the company as a whole, but does’t plan implemented CSR programs on community sustainability.